Leukemia inhibitory factor induces DNA synthesis in Swiss mouse 3T3 cells independently of cyclin D1 expression through a mechanism involving MEK/ERK1/2 activation - Dekanty, A. (2006)
Leukemia inhibitory factor (LIF) and oncostatin M (OSM) induce DNA synthesis in Swiss 3T3 cells through common signaling mechanism(s), whereas other related cytokines such as interleukin-6 and ciliary neurotrophic factor do not cause this response. Induction of DNA replication by LIF or prostaglandin F 2α (PGF 2α) occurs, in part, through different signaling events. LIF and OSM specifically trigger STAT1 cytoplasmic to nuclear translocation, whereas PGF 2α fails to do so. However, LIF and PGF 2α can trigger increases in ERK1/2 activity, which are required for their mitogenic responses because U0126, a MEK1/2 inhibitor, prevents both ERK1/2 activation and induction of DNA synthesis by LIF or PGF 2α treatment. PGF 2α induces cyclin D expression and full phosphorylation of retinoblastoma protein. In contrast, LIF fails to promote increases in cyclin D mRNA/protein levels; consequently, LIF induces DNA synthesis without promoting full phosphorylation of retinoblastoma protein (Rb). However, both LIF and PGF 2α increase cyclin E expression. Furthermore, LIF mitogenic action does not involve protein kinase C (PKC) activation, because a PKC inhibitor does not block this effect. In contrast, PKC activity is required for PGF 2α mitogenic action. More importantly, the synergistic effect between LIF and PGF 2α to promote S phase entry is independent of PKC activation. These results show fundamental differences between LIF and PGF 2α-dependent mechanism(s) that induce cellular entry into S phase. These findings are critical in understanding how LIF and other related cytokine-regulated events participate in normal cell cycle control and may also provide clues to unravel crucial processes underlying cancerous cell division. © 2006 by The American Society for Biochemistry and Molecular Biology, Inc.